An Artificial Breeding Site for Larvicide Bioassays and Interaction Studies with Diptera:Simuliidae and Other Macroinvertebrates from Lotic Systems - Figueiró, Ronaldo; Docile, Tatiana; Aranda, Árion (BioAssay, 2009)
This note presents an artifical breeding site, composed of a modified aquarium, which allows a wide range of controllable water discharge and water velocity variation. It is applicable for bioassays with Diptera: Simuliidae and interaction studies with other macroinvertebrates, as well as assessing impact of larvicides on nontarget organisms.